1991
DOI: 10.1210/endo-129-2-848
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phosphate Depletion Dissociates Hormonal Stimulated Second Messengers in Osteoblast-Like Cells*

Abstract: The acute effect (24 h) of either phosphate depletion or phosphate surfeit on hormonal stimulated signal transduction systems was studied in the osteoblastic cell line UMR-106. Elevation of intracellular Ca2+ ([Ca2+]in), induced by different calciotropic hormones (PTH, prostaglandin E2, endothelin) was blunted by acute phosphate depletion, whereas at high inorganic phosphate (Pi) concentrations the rise in [Ca2+]in was augmented. Basal [Ca2+]in was not altered by either Pi depletion or Pi excess. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Second, both classes of effects also had similar dependencies for phosphate--in both cases, an increase in the phosphate concentration in the medium was associated with a shifting of the fluoride dose-response curve to a range of lower levels. (Previous studies [15,39,40] have also reported similar P~ dependencies for 45Ca uptake and 3[H]-thymidine incorporation, and one recent study indicates that hormonemediated second messenger response (including effects on intracellular Ca) can be affected acutely by changes in the Pi concentration [41].) Finally, coincubation with verapamil prevented the actions of fluoride to increase net 45Ca uptake and 3[Hl-thymidine incorporation.…”
Section: Discussionmentioning
confidence: 66%
“…Second, both classes of effects also had similar dependencies for phosphate--in both cases, an increase in the phosphate concentration in the medium was associated with a shifting of the fluoride dose-response curve to a range of lower levels. (Previous studies [15,39,40] have also reported similar P~ dependencies for 45Ca uptake and 3[H]-thymidine incorporation, and one recent study indicates that hormonemediated second messenger response (including effects on intracellular Ca) can be affected acutely by changes in the Pi concentration [41].) Finally, coincubation with verapamil prevented the actions of fluoride to increase net 45Ca uptake and 3[Hl-thymidine incorporation.…”
Section: Discussionmentioning
confidence: 66%
“…However, in the absence of more direct assays of src activity, the possibility ofother intracellular TKs mediating 160-140-0 = 120-11 10 9 -LOG [PTHJ osteoblasts. Others and we have shown that the pleiotropic functions of these hormones on bone metabolism can be explained on the basis of antagonistic effects between the Ca2+ and cAMP signaling pathways (41)(42)(43)(44)56). With respect to cell growth, the cAMP messenger system is antiproliferative, while…”
Section: Methodsmentioning
confidence: 99%
“…It is now well established that the osteoblast plays a key role in both bone formation and bone resorption processes stimulated by osteotropic agents (39,40). Moreover, the Ca2' and cAMP messenger systems generated inside the osteoblastic cytosol mediate many of the effects of calciotropic hormones (41)(42)(43)(44). Given the in vivo observation of cooperativity between IL-6 and calciotropic hormones on bone remodeling, it is conceivable that the cytokine impinges on transduction pathways generated by hormones.…”
Section: Introductionmentioning
confidence: 99%
“…In osteoblastic cells, several studies demonstrated that hormones modulated VSCCs, included in parathyroid hormone (PTH) (Green et al, 1991;Li et al, 1997;Yamaguchi et al, 1987), bradykinin (Tokuda et al, 1994), 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) (Bergh et al, 2006;Uchida et al, 2012;Zanello et al, 2006) and phalloidin, a stabilizer of actin filaments (Li et al, 2011). To our knowledge, the data presented here demonstrate for the first time that IL-1β and -6 modulates VSCCs in osteoblasts.…”
Section: Discussionmentioning
confidence: 55%